Decision time is associated with future cooperation and social rewiring decisions in network public goods games - Zeyu Zhu (PLoS ONE, 2026)
Previous research suggests that encouraging cooperation in social networks by engaging cooperators with defectors is only effective when individual heterogeneity is considered. However, this heterogeneity remains largely underexplored. Drawing on the drift-diffusion model, decision time captures this heterogeneity as an indicator of the feeling of conflict when individuals make cooperation decisions. Using secondary data from a previous public goods game experiment, this study first investigates how one’s decision time predicts one’s cooperation decision in the next round. A typical participant with a longer decision time is more likely to flip their decision. I then explore the relationship between this decision time and one’s willingness to connect to others when offered a chance. Faster defectors are more willing to connect to both cooperators and defectors than slower defectors. Faster cooperators are less willing to connect to defectors than slower cooperators, but no significant difference is found between faster and slower cooperators when offered to connect to fellow cooperators after controlling for environmental factors. The findings may serve as a foundation for transparent intervention strategies that facilitate cooperation by selectively engaging cooperator–defector pairs.